Crescimento e rendimento em mamoeiro formosa em função de doses de boro, fósforo e zinco - Lima, Fabrício Ferreira (2014)
Papaya is a plant of rapid growth and continuous production and therefore requires a balanced nutrition. In this research three experiments were made under field conditions in Acaraú, CE, aiming to evaluate the growth, yield and mineral composition of the papaya plant stemming doses of B, P and Zn. In the first experiment, the treatments were arranged in factorial 4 x 4 + 1, being four B doses (0.5, 1.0, 2.0 and 4.0 kg ha-1) and four installments (P1 = 100 % of B fertilization at 30 days after planting (DAP), P2 = 50% at 30 DAP and 50% at 180 DAP; P3 = 50% at 30 DAP, 25% at 90 DAP and 25% at 180 DAP, and P4 = 100% to 180 DAP), plus a control (0 kg ha-1 B), in experimental design of randomized blocks with four replications. In the second experiment, the treatments were in a factorial 3 x 3 + 1, three P2O5 doses (100, 200 and 300 kg ha-1) and three installments (P1 = 100% of P fertilization at planting; P2 = 50% at planting and 50% at 180 DAP and P3 = 50% at planting, 25% at 90% DAP and 25% at 180 DAP), plus a control (0 kg ha-1 P2O5) in experimental design of randomized blocks with three replications. In the third experiment, treatments consisted of six Zn doses (7.8, 9.8, 11.8, 13.8, 15.8 and 19.8 kg ha-1) in experimental design of randomized blocks with three replications. Were evaluated plant height and girth stem at 180 DAP; B, P and Zn concentrations in the petiole leaf at 210 and 360 DAP and in the fruit at 240 DAP and the yield of papaya trees between 210 and 360 DAP. The experimental data were subjected to analysis of variance by F-test. To the B, P and Zn doses were adjusted regression equations and the B and P installments were applied Tukey test. The growth, the B, P and Zn concentration in the petiole leaf and the yield were affected by B, P and Zn doses. The maximum yields were achieved at doses 2 kg ha-1 of B, 160 kg ha-1 of P2O5 and 10 kg ha-1 of Zn. Already the B, P and Zn concentration in the petioles related maximum yield was 22 mg kg-1, 1.9 g kg-1 and 12 mg kg-1 at 210 DAP, respectively.